Enhancing Skill India Mission in Rajasthan: A Progressive Analysis and Roadmap for Improvement - Khandelwal, Naman; Singh, P.K; Gupta, Nidhi (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
The Skill India Mission, initiated by the Government of India, aims to empower the youth through skill development and employment opportunities. This research proposal focuses on assessing the progress of the Skill India Mission in Rajasthan and proposes strategies for further enhancement. The analysis identifies various positive aspects of the mission, such as the establishment of skill development centers, sector-specific training programs, industry collaborations, and recognition of prior learning. However, it also identifies areas requiring improvement. Recommendations include strengthening infrastructure, developing industry-driven curriculum, fostering more industry partnerships, focusing on rural areas, implementing effective monitoring and evaluation mechanisms, integrating soft skills training, conducting awareness and outreach campaigns, collaborating with educational institutions, promoting entrepreneurship development, and ensuring continuous skill upgradation. Implementing these measures can bolster the effectiveness of the Skill India Mission in Rajasthan, leading to improved skill development outcomes, enhanced employability, and sustainable economic growth.
Keywords: Skill India Mission; Rajasthan; progress; enhancement; skill development; employment; infrastructure; industry partnerships; rural areas